Corporate Governance Reform and CEO Compensation: Intended and Unintended Consequences - Matsumura, Ella Mae (Journal of business ethics, 2005)
Recent scandals allegedly linked to CEO compensation have brought executive compensation and perquisites to the forefront of debate about constraining executive compensation and reforming the associated corporate governance structure. We briefly describe the structure of executive compensation, and the agency theory framework that has commonly been used to conceptualize executives acting on behalf of shareholders. We detail some criticisms of executive compensation and associated ethical issues, and then discuss what previous research suggests are likely intended and unintended consequences of some widely proposed executive compensation reforms. We explicitly discuss the following recommendations for reform: require greater independence of compensation committees, require executives to hold equity in the corporation, require greater disclosure of executive compensation, increase institutional investor involvement in corporate governance (including executive compensation), and require firms to expense stock options on their income statements. We provide a brief summary discussion of ethical issues related to executive compensation, and describe possible future research.